2006
DOI: 10.1155/mi/2006/67120
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Interleukin‐18 in Modulation of Oral Carcinoma Cell Proliferation

Abstract: Interleukin-18 (IL-18), a proinflammatory cytokine, is produced by oral epithelia and carcinoma cells and implicated in tumor regression. Since its direct biological effect on oral cancer cells is not well defined, in this study, we employed a KB cell line to test IL-18 activity. Recombinant human IL-18 significantly inhibited KB cell proliferation in a dose-dependent fashion (P < .05) without increasing cytotoxicity. Analysis of its mode of action showed that IL-18 induced cell cycle arrest in the S phase; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that IL-18 exhibits significant antitumor activities by inducing IFN-γ expression in T cells and natural killer cells ( 29 ), by ectopic expression of hMSH2-induced oxidative stress ( 30 ), or via the modulation of cell cycle progression leading to S-phase arrest ( 31 ). Data of those studies on IL-18 antitumor activity are consistent with our results, indicating that IL-18 expression enhances the anticancer effects of TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IL-18 exhibits significant antitumor activities by inducing IFN-γ expression in T cells and natural killer cells ( 29 ), by ectopic expression of hMSH2-induced oxidative stress ( 30 ), or via the modulation of cell cycle progression leading to S-phase arrest ( 31 ). Data of those studies on IL-18 antitumor activity are consistent with our results, indicating that IL-18 expression enhances the anticancer effects of TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that C allele of IL-18 -137G/C polymorphisms lead to a lower level of IL-18 protein synthesis [ 9 ]. Such an occurrence impedes the modulation of cell cycle arrest and the triggering of cell apoptosis, which protects the host from oral cancer development [ 4 , 6 - 8 ]. Moreover, the inconsistent results between ours and those of Vairaktaris et al and Asefi et al, indicating the impaction of genetic polymorphism -137G/C on oral cancer susceptibility may be difference related to ethnicity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-18 ( IL-18 ), an 18-kDa cytokine, belongs to the interleukin-1 (IL-1) superfamily and is produced by various immune and non-immune cells [ 4 - 7 ]. It has been demonstrated that the expression and secretion of IL-18 is a crucial event against oncogenesis of oral carcinoma cells because of its modulation of cell cycle progression or its triggering of an apoptotic pathway [ 4 , 6 - 8 ]. Nilkaeo et al found that the IL-18 suppressed KB cell line, a carcinoma cell line derived from oral cavity, proliferates in a dose-dependent manner through the modulation of cell-cycle arrest in the S phase [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article titled “Role of Interleukin-18 in Modulation of Oral Carcinoma Cell Proliferation” [ 1 ], KB cells have been found to be cross-contaminated by HeLa cells [ 2 ], which means that KB is really a cervical cancer line and not an oral cancer line. Accordingly, no conclusions can be drawn relating specifically to oral cancer.…”
mentioning
confidence: 99%